2007
DOI: 10.1111/j.1365-2486.2007.01358.x
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Hurricane Frances on Florida scrub‐oak ecosystem processes: defoliation, net CO2 exchange and interactions with elevated CO2

Abstract: Hurricane disturbances have profound impacts on ecosystem structure and function, yet their effects on ecosystem CO 2 exchange have not been reported. In September 2004, our research site on a fire-regenerated scrub-oak ecosystem in central Florida was struck by Hurricane Frances with sustained winds of 113 km h À1 and wind gusts as high as 152 km h À1 . We quantified the hurricane damage on this ecosystem resulting from defoliation: we measured net ecosystem CO 2 exchange, the damage and recovery of leaf area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
61
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 69 publications
(102 reference statements)
9
61
2
Order By: Relevance
“…Our result of increased soil respiration 1 year after hurricane Wilma contrast with previous studies in which a reduction in soil respiration was observed following hurricane disturbances in tropical and subtropical forests [ Steudler et al , 1991; Li et al , 2007]. However, our study site suffered considerably more damage from a hurricane category IV compared to the hurricanes category I and II in those studies.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Our result of increased soil respiration 1 year after hurricane Wilma contrast with previous studies in which a reduction in soil respiration was observed following hurricane disturbances in tropical and subtropical forests [ Steudler et al , 1991; Li et al , 2007]. However, our study site suffered considerably more damage from a hurricane category IV compared to the hurricanes category I and II in those studies.…”
Section: Discussioncontrasting
confidence: 96%
“…Impacts of large, infrequent disturbances are among the most difficult events to study, as they are unpredictable in space and time, but are critical to understanding the functioning of ecosystems [ Turner and Dale , 1998]. Soils have usually been ignored while studying hurricane disturbances and this study is one of the first attempts to study soil CO 2 dynamics following a hurricane event [ Steudler et al , 1991; Li et al , 2007]. Furthermore this is the first study that report automated measurements and diel patterns of soil respiration in a seasonally dry tropical forest (SDTF).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McCarthy et al (2006) found that $20-year-old loblolly pine trees growing in elevated (ambient + 200 mmol mol À1 ) CO 2 were slightly more resistant to ice damage and recovered more quickly than trees in ambient CO 2 . In contrast, Li et al (2007) found that wind damage from Hurricane Frances was just as great on 8-year-old oak trees growing in elevated (ambient + 350 mmol mol À1 ) CO 2 as in ambient CO 2 . Uncertainties in how disturbance and physiology interact reduce the confidence investigators might have for predictions of forest productivity based solely on the physiology of trees and other co-occurring species.…”
Section: Tree Physiology In a Changing Atmosphere And Climatementioning
confidence: 82%
“…Multiple disturbances can cause a loss of leaves and/or fine roots, which limits the capacity to photosynthesize and take up nutrients and water and which may further reduce ecosystem gross primary production following disturbances (77,138). Defoliation studies have shown that NSC stores often decrease soon after defoliation (78,135).…”
Section: Experimental Manipulationsmentioning
confidence: 99%